A Soft Switching Single Phase Power Factor Correction AC-DC Boost Converter with Passive Snubber - Ting, Nairn Suleyman; Altintas, Nihan (IEEE, 2017)
This paper introduces a new soft switching single phase power factor correction (PFC) boost converter with passive snubber. In the proposed converter, the main switch is turned on under zero current switching (ZCS) and turned off under zero voltage switching (ZVS) owing to the proposed passive snubber. Besides, the main diode is turned on under ZVS and turned off under ZCS. The proposed converter has features such as low cost, simple control, low number of element and high power density. Also, the output current and voltage are controlled by the proposed PFC converter in wide line and load range. The operating modes of the proposed converter are presented in detail. Also, the simulation results of converter are obtained for 1 kW and 100 kHz. It is observed that the new proposed converter has 0.99 power factor with sinusoidal current shape. So, power factor quality is fairly high.
Keywords: passive snubber cell; power factor correction; zero-voltage transition; zero-current transition; soft switching; Engineering